Komunikasi Politik Pemerintah Susilo Bambang Yudhoyono (Sby) (Studi Kasus Masalah Bahan Bakar Minyak Tahun 2012) - Tukina, Tukina (Bina Nusantara University, 2013)
Price of international oil and gas has fluctuatively increased from time to time. The reality encourages the government of Susilo Bambang Yudhoyono (SBY) to raise (or adjust) the price of fuel in the country. Viewed from the history, since the era of President Soekarno, Soeharto, Megawati, and Gusdur fuel price increase policy has always been controversial, inviting pros and cons, although the actual adjustment is reasonable and necessary. Government policy of SBY to raise fuel prices and ultimately failed is interesting to learn. This study focused on the political communication of SBY government. The SBY government's efforts to raise fuel prices got tough challenge from several people, including members of the Parliament. The pros and cons protracted and eventually the SBY government failed to raise the fuel prices. Methodology of this article used descriptive-qualitative research. Data obtained through field observations and literature. Data were analyzed descriptively based on research purposes. Role of the writer in a descriptive qualitative study was the main thing. Results showed that the failure of SBY political communication was caused by the failure in convincing Indonesian people. SBY government needed to clarify and reinforce the authority to raise fuel prices belong to the Government. Any information (messages) should be communicated directly, clearly, and firmly through the process. Messages from the source to the target (society) needs to be maintained properly. If not, the messages can be misused. Each message can be added, subtracted (either partially or completely) which will lead to misunderstanding, biased, confusing, and protracting situasions.